Dampak Pandemi Covid-19 terhadap Aktivitas Fisik pada Mahasiswa Fakultas Keperawatan Universitas Padjadjaran - Audi Siti Sarah; Tuti Pahria; Iwan Shalahuddin (Malahayati Nursing Journal, 2023)
ABSTRACT The Covid-19 pandemic in Indonesia has led to restrictions on activities outside the home, the closure of public facilities, and the application of online learning which creates challenges for students to stay physically active. This study aimed to describe the impact of Covid-19 pandemic on physical activity in students of the Faculty of Nursing, Universitas Padjadjaran (Fkep Unpad) The purpose of this study was to describe the impact of the Covid-19 pandemic on physical activity in students of the Faculty of Nursing, Universitas Padjadjaran. This research is a quantitative descriptive study on 216 active students of Fkep Unpad class 2018 and 2019 who are taking online learning. Physical activity data were collected using the online International Physical Activity Questionnaire version of the Short Form (IPAQ-SF) which had been tested for validity and reliability. Physical activity was analyzed by looking at the distribution of physical activity before and during the Covid-19 pandemic on heavy, moderate, and walking physical activity. The category of physical activity was calculated by calculating the total Metabolic equivalents (METs) per week. The results showed that before the Covid-19 pandemic, the total weekly energy expenditure of students was 1844 METs-minutes/week with 78 students (36.1%) in the high category, 117 students (54.2%) in the medium category, and 21 students (9.7%) in the low category. Meanwhile, during the Covid-19 pandemic, students' total weekly energy expenditure was 1185 METs-minutes/week with 49 students (22.7%) in the high category, 101 students (46.8%) in the medium category, and 66 students (30.6%) ) in the low category There was a decrease in physical activity among Fkep Unpad students during the Covid-19 pandemic. However, during the Covid-19 pandemic, some samples managed to maintain a level of physical activity in the moderate category which is recommended during the Covid-19 pandemic. Students must do at least 30 minutes of physical activity every day. Keywords: Covid-19 Pandemic, Physical activity, University Students  ABSTRAK Pandemi Covid-19 di Indonesia menyebabkan pembatasan aktivitas di luar rumah, penutupan fasilitas umum, serta penerapan pembelajaran secara daring yang menyebabkan tantangan bagi mahasiswa untuk tetap beraktivitas fisik. Penelitian ini bertujuan untuk mengetahui gambaran dampak pandemi Covid-19 terhadap aktivitas fisik pada mahasiswa Fakultas Keperawatan Universitas Padjadjaran (Fkep Unpad). Tujuan dari penelitian ini adalah untuk menggambarkan dampak pandemi Covid-19 terhadap aktivitas fisik pada mahasiswa Fakultas Keperawatan Universitas Padjadjaran. Penelitian ini merupakan penelitian deskriptif kuantitatif pada 216 mahasiswa aktif Fkep Unpad angkatan 2018 dan 2019 yang sedang mengikuti pembelajaran daring. Data aktivitas fisik diambil menggunakan International Physical Activity Questionnaire versi Short Form (IPAQ-SF) secara online yang telah teruji validitas dan reliabilitasnya. Aktivitas fisik dianalisis dengan melihat sebaran aktivitas fisik sebelum dan selama pandemi Covid-19 pada aktivitas fisik berat, sedang, dan berjalan. Pengkategorian aktivitas fisik dilakukan dengan menghitung total Metabolic equivalents (METs) per minggu. Hasil penelitian menunjukkan sebelum pandemi Covid-19 total pengeluaran energi mingguan mahasiswa sebesar 1844 METs-menit/minggu dengan 78 mahasiswa (36,1%) berkategori tinggi, 117 mahasiswa (54,2%) berkategori sedang, dan 21 mahasiswa (9,7%) berkategori rendah. Sedangkan, selama pandemi Covid-19 total pengeluaran energi mingguan mahasiswa sebesar 1185 METs-menit/minggu dengan 49 mahasiswa (22,7%) berkategori tinggi, 101 mahasiswa (46,8%) berkategori sedang, dan 66 mahasiswa (30,6%) berkategori rendah. Terjadi penurunan aktivitas fisik pada mahasiswa Fkep Unpad selama pandemi Covid-19. Meskipun begitu, selama pandemi Covid-19 sebagian sampel berhasil mempertahankan tingkat aktivitas fisik pada kategori sedang yang dianjurkan pada masa pandemi Covid-19. Mahasiswa harus melakukan aktivitas fisik setidaknya 30 menit setiap hari.. Kata Kunci: Aktivitas Fisik, Mahasiswa, Pandemi Covid -19